In vitro biological screening of ethanol extract of Pterocarpus Indicus Willd. (Fabaceae) leaves - Rofiq, Md Osama Bin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.